2009
DOI: 10.1016/j.asr.2009.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric slab thickness – Analysis, modelling and monitoring

Abstract: A review of the climatological and storm-time behaviour of the ionospheric slab thickness is presented based on long-time observations at a European mid-latitude site, Dourbes (50.1°N, 04.6°E), and on published results from other studies. An operational electron density and slab thickness monitoring system, established to provide real-time characterisation of the local ionospheric dynamics, is outlined together with some exemplary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 36 publications
5
44
1
9
Order By: Relevance
“…Similar nature of variation was also reported earlier over Waltair, during a high solar activity period by Prasad et al (1987). The results obtained over Delhi are consistent with those obtained by Stankov and Warnant (2009) and Chuo et al (2010), in which a predawn enhancement in the slab-thickness and gradual disappearance from winter to summer at mid latitudes have been observed. The atmospheric neutral winds and enhanced eastward electric fields have significant and dominant influence on the peaks during these two periods (Chuo et al, 2010).…”
Section: Variation Of Equivalent Slab-thickness (τ )supporting
confidence: 81%
“…Similar nature of variation was also reported earlier over Waltair, during a high solar activity period by Prasad et al (1987). The results obtained over Delhi are consistent with those obtained by Stankov and Warnant (2009) and Chuo et al (2010), in which a predawn enhancement in the slab-thickness and gradual disappearance from winter to summer at mid latitudes have been observed. The atmospheric neutral winds and enhanced eastward electric fields have significant and dominant influence on the peaks during these two periods (Chuo et al, 2010).…”
Section: Variation Of Equivalent Slab-thickness (τ )supporting
confidence: 81%
“…In each season a daily variation in the northern hemisphere is rather more than in the southern hemisphere. It differs from results for summer in other papers, for example (Stankov and Warnant, 2009). Pre-dawn maximums of s are accurately visible during all seasons in subauroral areas.…”
Section: Results Of S(med) Comparison With Experimental Datacontrasting
confidence: 70%
“…It was revealed that the slab thickness varies with diurnal, seasonal, geomagnetic and solar activity. Stankov and Warnant (2009) described the climatological and storm-time behaviour of the slab thickness based on long-term observations at a European mid-latitude site (Dourbes), which further confirmed the expected diurnal, seasonal, and geomagnetic dependency. Guo et al (2011) reported the latitudinal variation in the slab thickness using global ionospheric maps (GIMs) and the Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC).…”
Section: Introductionmentioning
confidence: 73%
“…Bhonsle et al, 1965;Titheridge, 1973;Huang, 1983). Based on most of the available and reliable observations of ionospheric TEC and NmF2, numerous analyses for recording the climatology of the slab thickness have been conducted over the past few decades (Jayachandran et al, 2004;Chuo, 2007;Jin et al, 2007;Stankov and Warnant, 2009;Guo et al, 2011;Kenpankho et al, 2011;Weng et al, 2012). Jayachandran et al (2004) investigated the variation in the slab thickness during the solar maximum and minimum phases of an intense solar cycle by using the hourly values of TEC and NmF2 at Hawaii (low latitude), Boulder (mid-latitude) and Goosebay (high latitude).…”
Section: Introductionmentioning
confidence: 99%